Perancangan Sistem Automatic Storage and Retrieval System untuk Automasi Persediaan Sistem Pergudangan - Grant Juan Viano; Sudaryanto Sudaryanto (Jurnal Syntax Admiration, 2024)
Inventory is an important thing in a company. A good inventory system will of course support other aspects so that the company can operate smoothly. Errors that occur in the inventory system can certainly be detrimental to the company, both intentional and unintentional errors. Efforts to minimize these errors can be done by implementing automation, where automation can reduce errors that may be made by humans so that inventory data can be monitored more accurately, can reduce the need for labor, and can reduce costs in the long term. Work that is routine and repetitive is work that is suitable for automation. The application of automation in a warehousing system can be used to move goods from one place to another, and can also pick up or store goods automatically using computer control. Inventory that is integrated with computers can monitor the quantity of goods available at any one time accurately and quickly, which is important for a company. Automatic storage and retrieval system (AS/RS) is a system that can carry out material retrieval and storage of materials automatically using computer control. This research contains about creating an AS/RS system for inventory automation along with how to control the system. The AS/RS system in this research involves moving material with color identification.